Isolation and Preliminary X-Ray Crystallographic Characterisation of the Periplasmic Ligand-Binding Domain of the Chemoreceptor Tlp3 from Campylobacter hepaticus - Diana Kovaleva; Yue Xin; Mohammad F. Khan; Yu H. Chin; Anna Roujeinikova (Crystals, 2025)
The Campylobacter genus includes many pathogenic species, with Campylobacter hepaticus primarily implicated in spotty liver disease in poultry. Chemotaxis is one of the well-established mechanisms of pathogenesis of Campylobacter. The chemoreceptor Tlp3, previously studied in C. jejuni, mediates responses to diverse ligands. Differences between the ligand-binding pockets of Tlp3s in C. hepaticus and C. jejuni may influence ligand specificity and niche adaptation. Here, we report a method for production of the ligand-binding domain of C. hepaticus Tlp3 (Ch Tlp3-LBD) in Escherichia coli inclusion bodies that yields crystallisable protein. Size-exclusion chromatography analysis showed Ch Tlp3-LBD is a monomer in solution. Ch Tlp3-LBD was crystallised using PEG 6000 and LiCl as the precipitants. The crystal lattice symmetry was P2221, with unit cell geometry of a = 82.0, b = 137.7, c = 56.1 Å, and α = β = γ = 90°. X-ray diffraction data have been acquired to 1.6 Å resolution using synchrotron radiation. Estimation of the Matthews coefficient (VM = 2.8 Å3 Da−1) and the outcome of molecular replacement suggested the asymmetric unit is composed of two protein molecules. This work lays the foundation for studies towards understanding the structural basis of ligand recognition by C. hepaticus Tlp3 and its role in pathogenesis.